2015
DOI: 10.1111/pedi.12330
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of diabetes education in children and adolescents with type 1 diabetes in Germany and Austria: analysis based on the German/Austrian DPV database

Abstract: Training frequency was highest in younger patients and during the first year of diabetes. Acute complications resulted in more frequent diabetes training, indicating that currently many education sessions take place in consequence to these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Whereas outpatient/home care of newly diagnosed T1D is the rule in the US or in Australia, hospitalization at T1D onset is common in Germany [4]. Moreover, pediatric diabetes education programs or therapy adjustment are frequently offered as inpatient care in Germany [9,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas outpatient/home care of newly diagnosed T1D is the rule in the US or in Australia, hospitalization at T1D onset is common in Germany [4]. Moreover, pediatric diabetes education programs or therapy adjustment are frequently offered as inpatient care in Germany [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, in many countries with a high hospitalization rate for pediatric diabetes, most of inpatient cases are not due to T1D complications [1,7,8]. In Germany for instance, elective hospital admissions for T1D without complications, like management of newly diagnosed diabetes, diabetes education or insulin dose adjustment, represent most of the inpatient cases in pediatric diabetes [1,7,9]. Among other things, hospitalization can be necessary for the implementation of multimodal therapy concepts, for pre/postprandial and nocturnal glucose monitoring, or for the reimbursement of multidisciplinary education programs for the patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…CGMS includes real-time CGM and CGM with intermittent scanning, also called "flash glucose monitoring." Diabetes education was documented if a teaching session lasted for at least 45 min and if the patient and/or members of his or her family or other caregivers participated (21).…”
Section: Indicators Of Diabetes Carementioning
confidence: 99%
“…We found that patients with lower SES were admitted more frequently to the hospital and tended to stay longer, even though the rate of acute complications (severe hypoglycemia, DKA) was not higher than in patients with medium or higher SES. Although there was no difference among participants with different levels of SES in diabetes education attendance, more hospital admissions and longer hospital stays among patients with lower SES may reflect the fact that these patients receive individual coaching by the diabetes teams in addition to regular diabetes education . Furthermore, they may be admitted earlier to prevent acute complications.…”
Section: Discussionmentioning
confidence: 92%